The Impact of Physical Activity on Retinal Health and Various Retinal Diseases - Kwiatkowska, Magdalena; Majta, Gabriela; Kusy, Sara (Quality in Sport, 2025)
Introduction: The health benefits of physical activity (PA) are widely known. Currently, its role in maintaining the health of the retina and in treating various diseases of the eye is being intensively studied, which are becoming an increasingly serious public health concern. Purpose of the Work: The aim of this study is to systematize knowledge about the impact of PA on retinal health and to raise awareness of this issue among the public and healthcare professionals. Materials and Methods: This paper is based on a comprehensive review of scientific research conducted worldwide. In the searching process the terms “retina”, “physical activity”, “ocular diseases”, “glaucoma”, “diabetic retinopathy” and “oxidative stress” were used. Results: PA has the potential to counteract microvascular regeneration, promote the body’s antioxidant capabilities and enhance anti-inflammatory responses. The protective effect has been observed in both physiological and pathological conditions. Conclusions: PA represents a promising strategy for maintaining retinal health and preventing the progression of various retinal diseases, and may improve the approach to their treatment. Therefore, further research is necessary to establish optimal guidelines regarding the type and intensity of exercise in the context of retinal diseases.